Image display panel and image display device

By designing a flat end surface, an adhesive layer with appropriate oleic acid swelling and a transparent protective film on the image display panel, combining silane coupling agent, and setting an external frame with an elastic intermediate layer, the grease of the image display panel in a humidified environment is solved. , the adhesive layer peeling problem caused by contact of paste components improves the durability and moisture resistance of the panel.

CN113168044BActive Publication Date: 2024-12-24NITTO DENKO CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN201980081208.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-17
Filing Date
2019-09-12
Publication Date
2024-12-24
Estimated Expiration
2039-09-12

AI Technical Summary

Technical Problem

When using open-closed image display devices such as laptops, the visible side surface strength of the image display panel is insufficient, and the contact of grease and paste components in the humidified environment causes the adhesive layer to expand and peel off the adhesive layer. Technology is difficult to solve effectively.

Method used

Design an image display panel with a flat end face shape, including a polarizing film and an adhesive layer, with an oleic acid swelling of the adhesive layer between 130% and 190%, equipped with a transparent protective film and a silane coupling agent , the outer frame is set through the elastic intermediate layer to prevent grease and paste components from directly contacting the adhesive layer.

Benefits of technology

The peeling of the adhesive layer is effectively suppressed, the durability and moisture resistance of the image display panel are improved, and the impact on other optical components is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113168044B_ABST
    Figure CN113168044B_ABST
Patent Text Reader

Abstract

The image display panel of the present invention comprises: an image display portion, and an optical film including a polarizing film, wherein the optical film is arranged on the visible side of the image display portion via an adhesive layer, wherein the oleic acid swelling degree of the adhesive layer is greater than 130% and less than 190%, and the end face of the image display panel is formed into a plane. The image display panel of the present invention can suppress peeling of the adhesive layer even in a humidified environment where grease or paste components are in contact with the elastic intermediate layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an image display panel, which can be used to form an image display device such as a liquid crystal display device (LCD) or an organic EL display device. Background Art

[0002] Image display panels such as liquid crystal display panels have a polarizing film disposed on an image display portion such as a liquid crystal cell according to the image forming method thereof. In general, in an image display panel, at least a polarizing film is bonded to the image display portion via a pressure-sensitive adhesive layer.

[0003] When forming the above-mentioned adhesive layer, an adhesive containing a base polymer and a cross-linking agent is usually used. As the above-mentioned base polymer, an acrylic adhesive using an acrylic polymer is used. Such an adhesive is required to have removability (reoperability) that allows easy peeling even when the polarizing film is attached to the image display portion in the wrong bonding position or when foreign matter bites into the bonding surface. In addition to reoperability, the above-mentioned adhesive layer is also required to improve white spots (peripheral unevenness) and improve durability. As an adhesive composition that can improve the above-mentioned characteristics, it is proposed to mix a polyether compound having a reactive silyl group in an acrylic polymer (Patent Document 1).

[0004] In addition, the image display panel is usually provided with a frame (outer frame) outside the panel from the viewpoint of handling etc. In recent years, design properties have been emphasized, and there is a tendency to narrow the frame (Patent Documents 2 and 3).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2010-275522

[0008] Patent Document 2: Japanese Patent Application Publication No. 2012-014000

[0009] Patent Document 3: Japanese Patent Application Publication No. 2016-004214 Summary of the invention

[0010] Problems to be solved by the invention

[0011] In addition, when the image display panel obtained by narrowing the frame is used in an image display device such as a mobile phone, a cover glass or the like is arranged on the outermost surface of the image display panel. However, when it is used in an open-and-close image display device such as a notebook computer, since a cover glass or the like is usually not arranged on the outermost surface of the image display panel, the strength of the visible side surface of the image display panel cannot be said to be sufficient. As a countermeasure, when using a notebook computer, etc., in order to prevent the image display panel from directly contacting the main body of the image display device when the laptop is closed, an elastomer is provided on the upper part of the frame, for example. However, when the frame is narrowed, it is sometimes difficult to provide the elastomer on the upper part of the frame. Therefore, a method of providing an elastic intermediate layer protruding from the outermost surface of the visible side of the image display panel between the end face of the image display panel and the frame when a narrow frame is used has also been studied.

[0012] Generally speaking, when opening and closing the image display panel in a notebook computer, etc., in most cases, the outer edge of the image display panel is touched by hand. There will be oil components (oleic acid, etc.) based on sebum on the hands, and after using moisturizing cream, sunscreen cream, etc., there are cases where the components of these creams remain on the hands. It is known that in such a case, if a notebook computer with a framed image display panel provided with the above-mentioned elastic intermediate layer is opened and closed by hand, there is a concern that the above-mentioned grease and paste components will directly or indirectly reach the adhesive layer that adheres the polarizing film, etc. to the image display part along the above-mentioned elastic intermediate layer, and the above-mentioned adhesive layer absorbs the above-mentioned components and expands. Especially in a humidified environment, the adhesive layer that absorbs the above-mentioned components is easy to expand, and there is a problem that the above-mentioned adhesive layer is peeled off from the image display part. However, the adhesive layer formed by the adhesive composition described in the above-mentioned patent document 1 cannot solve the above-mentioned peeling problem.

[0013] The object of the present invention is to provide an image display panel comprising: an image display portion, and a polarizing film arranged on the visible side of the above-mentioned image display portion via an adhesive layer, and the image display panel is applied in the form of a framed image display panel provided with an outer frame via an elastic intermediate layer, and the peeling of the above-mentioned adhesive layer can be suppressed even when placed in a humidified environment where grease or paste components are in contact with the above-mentioned elastic intermediate layer.

[0014] Another object of the present invention is to provide an image display device using the above-mentioned image display panel. Another object of the present invention is to provide an optical film with a pressure-sensitive adhesive layer that can be used in an image display device.

[0015] Solutions to the problem

[0016] The present inventors have conducted intensive studies to solve the above problems, and as a result, have found that the above problems can be solved by the following image display panel, etc., thereby completing the present invention.

[0017] That is, the present invention relates to an image display panel having:

[0018] An image display unit, and

[0019] An optical film including a polarizing film, wherein the optical film is disposed on the visible side of the image display portion via an adhesive layer.

[0020] The oleic acid swelling degree of the adhesive layer is greater than 130% and less than 190%,

[0021] The end surface of the image display panel is formed into a flat surface.

[0022] In the image display panel, it is preferred that the polarizing film has a transparent protective film on one or both sides of a polarizer, and the thickness of the polarizer is 3 to 30 μm.

[0023] In the image display panel, the optical film preferably has a surface treatment layer on the outermost surface on the viewing side.

[0024] In the image display panel, the distance from the outermost surface on the visible side of the image display panel to the pressure-sensitive adhesive layer is preferably 75 μm or more and 300 μm or less.

[0025] In the image display panel, the pressure-sensitive adhesive layer preferably has a thickness of 10 to 30 μm.

[0026] In the image display panel, the pressure-sensitive adhesive layer is preferably formed of a pressure-sensitive adhesive composition containing a (meth)acrylic polymer (A) as a base polymer. The pressure-sensitive adhesive composition preferably contains a silane coupling agent (B).

[0027] The image display panel may be used in the form of a framed image display panel in which an outer frame is provided outside an end surface of the image display panel.

[0028] In addition, the image display panel with a frame can be used in a manner in which the outer frame is provided on at least a portion of the outer side of the end surface of the image display panel through the outermost elastic intermediate layer protruding from the visible side of the image display panel without covering the elastic intermediate layer.

[0029] The framed image display panel may be used in a manner such that an end surface of the image display panel is in contact with the elastic intermediate layer.

[0030] The framed image display panel may be used in a mode where an inner frame is provided on the outermost surface of the end surface portion of the image display panel which is located inside the elastic intermediate layer, and the elastic intermediate layer protrudes from the inner frame.

[0031] The framed image display panel may be used in a manner such that an end surface of the image display panel is in contact with the elastic intermediate layer.

[0032] The framed image display panel may be used in a mode where an inner frame is provided on the outermost surface of the end surface portion of the image display panel which is located inside the elastic intermediate layer, and the elastic intermediate layer protrudes from the inner frame.

[0033] Furthermore, the present invention relates to a liquid crystal display device having the above-mentioned image display panel (or image display panel with a frame).

[0034] The present invention also relates to an optical film with a pressure-sensitive adhesive layer, which is disposed on a visible side of an image display portion.

[0035] The optical film with an adhesive layer comprises an optical film including a polarizing film, and an adhesive layer.

[0036] The adhesive layer has a degree of swelling in oleic acid of greater than 130% and less than or equal to 190%.

[0037] Effects of the Invention

[0038] As an image display panel, an image display panel having an image display portion and an optical film including a polarizing film disposed on the visible side of the image display portion via an adhesive layer is generally used. As such, the image display panel is a laminate of a plurality of different components, and therefore, from the perspective of ease of manufacture, processability, and handling, the image display portion in the image display panel is larger than the adhesive layer and the optical film (see Figure 2A Therefore, it is believed that when the grease or paste component enters the end surface of the image display panel, the grease or paste component remains on the image display panel in the form of a liquid pool and is in contact with the adhesive layer. For this reason, the adhesive layer is peeled off from the image display portion (refer to Figure 2B ).

[0039] On the other hand, the image display panel of the present invention is a laminate of a plurality of different members as described above, but the end faces are formed into a single plane, so there is no height difference between the members and they are flat (see Figure 1A ). For the image display panel of the present invention, even if grease or paste components enter the end surface of the image display panel, the grease or paste components will uniformly pass through or be dispersed on the end surface of the image display panel (refer to Figure 1B). Therefore, according to the image display panel of the present invention, the contact frequency with the adhesive layer can be reduced compared with the conventional end face whose end face is not a flat surface, and the above-mentioned adhesive layer can be prevented from peeling off from the image display part even in a humidified environment.

[0040] In addition, the image display panel of the present invention can be applied in the form of a framed image display panel provided with an external frame, and it is particularly preferred that the framed image display panel of the present invention has a structure in which an external frame is provided on the image display panel via an elastic intermediate layer. In addition, for the framed image display panel of the present invention, by setting the distance from the outermost surface of the visible side of the above-mentioned image display panel to the adhesive layer attached to the visible side of the image display portion to be above a given range, even when grease or paste components contact the above-mentioned elastic intermediate layer, the above-mentioned components can be prevented from reaching the above-mentioned adhesive layer and contacting it to a certain extent. In addition, the framed image display panel of the present invention is formed of an adhesive composition containing an acrylic polymer as a base polymer and a given silane coupling agent to form the above-mentioned adhesive layer, and the above-mentioned acrylic polymer uses a given monomer at a given ratio or above, so that even in a humidified environment where grease or paste components contact the above-mentioned elastic intermediate layer, the peeling of the adhesive layer can be suppressed.

[0041] In addition, in the image display panel of the present invention, the oleic acid swelling degree of the above-mentioned adhesive layer is controlled to be greater than 130% and less than 190%. Therefore, the above-mentioned adhesive layer can absorb oil and paste components to reduce the impact on other optical components (films, substrates, wirings, etc. on the lower side of the panel). BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1A This is a partial cross-sectional view showing an example of the image display panel of the present invention.

[0043] Figure 1B This is a partial cross-sectional view showing an example of a state in which grease or the like has entered the end surface of the image display panel of the present invention.

[0044] Figure 2A This is a partial cross-sectional view showing an example of a conventional image display panel.

[0045] Figure 2B This is a partial cross-sectional view showing an example of a state in which grease or the like has entered the end surface of the image display panel of the present invention.

[0046] Figure 3A This is a partial cross-sectional view showing an example of a framed image display panel of the present invention.

[0047] Figure 3B It is shown Figure 3A A top view of an example of a framed image display panel of the present invention.

[0048] Figure 4A This is a partial cross-sectional view showing an example of a framed image display panel of the present invention.

[0049] Figure 4B It is shown Figure 4A A top view of an example of a framed image display panel of the present invention.

[0050] Figure 5 This is a partial cross-sectional view showing an example of a framed image display panel according to a comparative example.

[0051] Explanation of symbols

[0052] A Image display panel

[0053] 1 Image display unit

[0054] 2 Optical films (including polarizing films)

[0055] 3 Adhesive layer (image display side)

[0056] 4 Elastic middle layer

[0057] 5 External border

[0058] 6 Inner border

[0059] 7 empty rooms

[0060] 8 Adhesive layer (cover glass side)

[0061] 9 Cover glass DETAILED DESCRIPTION

[0062] Hereinafter, the present invention will be described with reference to the accompanying drawings.

[0063] like Figure 1A As shown in the cross-sectional view of , the image display panel A of the present invention comprises: an image display portion 1, and an optical film 2 disposed on the visible side of the image display portion 1 via an adhesive layer 3. The end faces b (respectively b1, b2, b3) of the image display panel A are formed into a single plane. Figure 1B The state where the grease or paste component s has entered the end surface b is shown.

[0064] It should be noted that if Figure 2A As shown in the cross-sectional view, the existing image display panel A' comprises: an image display part 1, and an optical film 2 arranged on the visible side of the image display part 1 via an adhesive layer 3, but the image display part 1 is larger than the adhesive layer 3 and the optical film 2, and the end faces b (b1, b2, b3 respectively) of the image display panel A' are not a single plane. Figure 1B The state where the grease or paste component s has entered the end surface b is shown.

[0065] In addition, for the image display panel of the present invention, it is preferred that the distance t from the outermost surface a of the visible side of the image display panel A (optical film 2) to the adhesive layer 3 be set to be greater than 75 μm. From the perspective of suppressing the peeling of the adhesive layer 3 caused by grease and paste components, it is preferred that the distance t be set to be greater than 75 μm. From the perspective of suppressing the peeling of the adhesive layer 3, the distance t is preferably greater than 100 μm, and more preferably greater than 120 μm. On the other hand, when the distance t becomes longer (that is, when the thickness of the optical film becomes thicker), there is a tendency for the optical film to shrink in size in a humidified environment and become more prone to warping. Therefore, the distance t is preferably less than 300 μm, and more preferably less than 250 μm.

[0066] The image display panel of the present invention can be applied in the form of a framed image display panel having an outer frame. The framed image display panel is, for example, Figure 3A As shown in the cross-sectional view of , an outer frame 5 is provided on the outer side of the end surface of the above-mentioned image display panel A. Figure 3A This is a partial cross-sectional view showing an example of an image display panel with a frame, showing an end side portion on one side. Figure 3B It is a top view of the image display panel with a frame of the present invention. An external frame 5 is provided across an elastic intermediate layer 4. The elastic intermediate layer 4 is provided to protrude from the outermost surface a of the visible side of the above-mentioned image display panel A (optical film 2), and the external frame 5 is provided in a manner not to cover the elastic intermediate layer 4. From the viewpoints of narrowing the frame, expanding the display area, preventing the infiltration of moisture, grease, and paste components, and preventing cracks from appearing at the end of the image display panel when the overall thickness of the image display device is reduced, it is preferred that the end face of the above-mentioned image display panel A is used in a manner in contact with the above-mentioned elastic intermediate layer 4. The above-mentioned external frame 5 can be fixed to the above-mentioned elastic intermediate layer 4 by an adhesive.

[0067] In addition, if Figure 4A As shown in the cross-sectional view of the present invention, the image display panel with a frame of the present invention can be Figure 3A In addition to the above-mentioned embodiment, an inner frame 6 is further provided on the outermost surface a of the end face of the image display panel A, which is closer to the inner side than the elastic intermediate layer 4. In this embodiment, the elastic intermediate layer 4 is also used in a manner protruding from the inner frame 6. Figure 3A In the embodiment shown in the figure, the case where the cavity 7 is provided between the end surface of the image display panel A and the elastic intermediate layer 4 is exemplified, but in Figure 4A In the manner shown, the image display panel A may be used in a manner such that the end surface of the image display panel A contacts the elastic intermediate layer 4. Figure 4AIn the case where the empty chamber 7 is provided in the manner shown, accessories (camera lens, wiring, dimming sensor, facial recognition sensor, etc.) can be arranged at the position of the empty chamber 7 so as to function through the internal frame 6 thereon. The internal frame 6 can be fixed to the outermost surface a of the image display panel A and the elastic intermediate layer 4 by an adhesive.

[0068] In addition, from the perspective of narrowing the frame of the image display panel with a frame, it is preferred that the widths of the outer frame 5 and the elastic intermediate layer 4 are both small. The widths of the outer frame 5 and the elastic intermediate layer 4 are appropriately set according to the size of the image display panel A. Usually, the width of the outer frame 5 is less than 5 mm, preferably 0.5 to 5 mm, and more preferably 0.5 to 3 mm. In addition, the width of the elastic intermediate layer 4 is less than 5 mm, preferably 0.5 to 5 mm, and more preferably 0.5 to 3 mm. In addition, regarding the inner frame 6, from the perspective of narrowing the frame, it is also preferred to be small. Usually, the width of the inner frame 6 is preferably 1 to 20 mm, and more preferably 1 to 15 mm. In addition, when the empty chamber 7 is provided, its width is preferably 1 to 20 mm, and more preferably 1 to 15 mm.

[0069] In addition, in the above Figure 3A In the embodiment shown in the figure, the elastic intermediate layer 4 is used in a manner protruding from the outermost surface a of the visible side of the image display panel A (optical film 2). Figure 4A In the embodiment shown, the elastic intermediate layer 4 is used in a manner protruding from the inner frame 6. This protrusion can prevent the image display panel from directly contacting the main body of the image display device. The height of the protrusion is usually preferably 0.5 to 5 mm, more preferably 0.5 to 3 mm. Figure 3B The top view shown, Figure 4B In the plan view shown, the elastic intermediate layer 4 is provided on the entire outer side of the end surface of the image display panel A. However, the present invention is also effective when the elastic intermediate layer 4 is provided on at least a portion.

[0070] <Optical film>

[0071] The optical film of the present invention is described below. As described above, the optical film of the present invention includes a polarizing film. The optical film of the present invention can be formed by a polarizing film alone, or can be formed in the form of a laminated optical film in which a polarizing film and other films are combined. In the framed image display panel of the present invention, the thickness of the optical film (also in the case of a laminated optical film) is designed so that the distance t satisfies 75 μm or more.

[0072] Polarizing film

[0073] The polarizing film contained in the above-mentioned optical film usually uses a polarizing film having a transparent protective film on one or both sides of the polarizer. The polarizer is not particularly limited, and various polarizers can be used. As the polarizer, for example, dichroic substances such as iodine and dichroic dyes are adsorbed on hydrophilic polymer films such as polyvinyl alcohol films, partially formalized polyvinyl alcohol films, and partially saponified films of ethylene-vinyl acetate copolymers and then uniaxially stretched, polyene oriented films such as dehydrated products of polyvinyl alcohol and dehydrochlorinated products of polyvinyl chloride, etc. are listed. Among them, preferred are polarizers formed by dichroic substances such as polyvinyl alcohol films and iodine. The thickness of these polarizers is not particularly limited, and is generally about 30μm or less.

[0074] In addition, as a polarizer, it is preferred to use a thin polarizer with a thickness of 3 to 30 μm. From the perspective of suppressing the peeling of the adhesive even in a humidified environment where there is a concern that grease and paste components may come into contact with the elastic intermediate layer, the thickness of the polarizer is preferably 3 μm or more. In addition, from the perspective of suppressing dimensional shrinkage in a humidified environment, the thickness of the polarizer is preferably 10 μm or less. A thin polarizer with a thickness of 3 to 10 μm has less thickness unevenness, excellent visual recognition, and less dimensional change, and therefore has excellent durability. Furthermore, the thickness of the polarizing film can also be thinned, and is therefore preferred in this respect.

[0075] As the material constituting the transparent protective film, for example, a thermoplastic resin having excellent transparency, mechanical strength, thermal stability, moisture barrier property, isotropy, etc. can be used. Specific examples of such thermoplastic resins include cellulose resins such as cellulose triacetate, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth) acrylic resins, cyclic polyolefin resins (norbornene resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. It should be noted that a transparent protective film can be attached to one side of the polarizer through an adhesive layer, and a thermosetting resin or ultraviolet curing resin such as (meth) acrylic acid, urethane, acrylic urethane, epoxy, silicone, etc. can be used as a transparent protective film on the other side.

[0076] As the material of the above-mentioned transparent protective film, cellulose resin and (meth) acrylic resin are preferred. As the (meth) acrylic resin, it is preferred to use a (meth) acrylic resin having a lactam ring structure. As the (meth) acrylic resin having a lactam ring structure, there can be cited (meth) acrylic resins having a lactam ring structure described in Japanese Patent Publication No. 2000-230016, Japanese Patent Publication No. 2001-151814, Japanese Patent Publication No. 2002-120326, Japanese Patent Publication No. 2002-254544, Japanese Patent Publication No. 2005-146084, etc. In particular, from the perspective of effectively suppressing the polarizer cracks that become a problem in the single-sided protective polarizing film having a transparent protective film only on one side of the polarizer, cellulose resin is preferred over (meth) acrylic resin. The thickness of the above-mentioned transparent protective film is usually preferably 10 to 100 μm, more preferably 20 to 50 μm. In particular, when a cellulose resin is used as the material of the transparent protective film, the thickness is preferably controlled to 100 μm or less from the viewpoint of suppressing dimensional shrinkage in a humid environment.

[0077] The adhesive used to bond the polarizer and the transparent protective film is not particularly limited as long as it is optically transparent. Various forms of adhesives such as aqueous, solvent-based, hot melt, free radical curing, and cation curing can be used, preferably aqueous adhesives or free radical curing adhesives.

[0078] 《Surface treatment layer》

[0079] A surface treatment layer may be provided on the outermost surface of the optical film. As the surface treatment layer, functional layers such as a hard coating layer, an anti-reflection layer, an anti-adhesion layer, a diffusion layer or an anti-glare layer may be cited. In addition to being provided on the transparent protective film of the polarizing film, the surface treatment layer may also be provided on other substrates different from the transparent protective film. Other substrates may use the same ones as the transparent protective film. In the case where a surface treatment layer is provided separately, it may be attached to the polarizing film using an existing known adhesive layer or the like.

[0080] For the material forming the hard coat layer provided as the surface treatment layer, for example, thermoplastic resins and materials cured by heat or radiation can be used. As the above-mentioned materials, radiation curing resins such as thermosetting resins, ultraviolet curing resins, and electron beam curing resins can be cited. Among them, ultraviolet curing resins that can efficiently form a cured resin layer by simple processing operations in the curing treatment using ultraviolet irradiation are preferred. As these curing resins, various resins such as polyesters, acrylics, urethanes, amides, silicones, epoxies, and melamines can be cited, including their monomers, oligomers, polymers, etc. From the viewpoint of fast processing speed and less damage to the substrate caused by heat, radiation curing resins are particularly preferred, and ultraviolet curing resins are particularly preferred. The ultraviolet curing resins preferably used can include, for example, resins having ultraviolet polymerizable functional groups, including monomers and oligomer components of acrylics having 2 or more, especially 3 to 6, of the functional groups. In addition, a photopolymerization initiator can be added to the ultraviolet curing resin.

[0081] In addition, as the above-mentioned surface treatment layer, an anti-glare treatment layer and an anti-reflection layer for improving visibility can be provided. In addition, an anti-glare treatment layer and an anti-reflection layer can be provided on the above-mentioned hard coating layer. The constituent material of the anti-glare treatment layer is not particularly limited, for example, radiation curing resin, thermosetting resin, thermoplastic resin, etc. can be used. As the anti-reflection layer, titanium oxide, zirconium oxide, silicon oxide, magnesium fluoride, etc. can be used. The anti-reflection layer can be provided with multiple layers. In addition, as the surface treatment layer, an anti-adhesion layer, etc. can be cited.

[0082] Other Layers

[0083] In the above optical film (laminated optical film), in addition to the above layers, a phase difference film (including 1 / 2, 1 / 4 wave plates), a visual compensation film, etc. can also be laminated. In addition, a tackifying layer or an easy-adhesion layer can be provided on the above polarizing film or other optical layers, or various easy-adhesion treatments such as corona treatment and plasma treatment can be applied to them.

[0084] <Adhesive layer>

[0085] Hereinafter, the pressure-sensitive adhesive layer for bonding the optical film to the image display unit will be described.

[0086] The above-mentioned adhesive composition preferably uses a transparent material with adhesiveness that can be used for optical purposes. As the above-mentioned adhesive composition, it can be suitably selected to use from, for example, acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives, and polyether adhesives. From the viewpoints such as transparency, processability and durability, it is preferred to use acrylic adhesives. Use a base polymer corresponding to the type of the above-mentioned adhesive composition. In the present invention, it is preferred to contain (methyl) acrylic polymer (A) as an acrylic adhesive of the base polymer.

[0087] The acrylic adhesive may include, for example, a partial polymer of a monomer component containing an alkyl (meth)acrylate and / or a (meth)acrylic polymer (A) obtained from the monomer component. It should be noted that (meth)acrylate refers to acrylate and / or methacrylate, and (meth) in the present invention has the same meaning.

[0088] The adhesive layer of the present invention is preferably formed from an adhesive composition containing a (meth)acrylic polymer (A) as a base polymer, wherein the (meth)acrylic polymer (A) contains 80 wt % or more of an alkyl (meth)acrylate (a) having an alkyl group having 1 to 4 carbon atoms as a monomer unit.

[0089] As the alkyl group in the (meth)acrylic acid alkyl ester (a) having an alkyl group having 1 to 4 carbon atoms constituting the main skeleton of the (meth)acrylic polymer (A), there can be exemplified linear or branched alkyl groups, such as methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, etc. As a monomer unit, the weight ratio of the (meth)acrylic acid alkyl ester (a) having an alkyl group having 1 to 4 carbon atoms is 80 weight % or more in the weight ratio of all the constituent monomers (100 weight %) constituting the (meth)acrylic polymer (A). By using the (meth)acrylic polymer (A) in the above ratio, it is preferable that the peeling of the adhesive layer can be suppressed even in a humidified environment where there is a concern that oils and fats and paste components will come into contact with the elastic intermediate layer.

[0090] As the alkyl (meth)acrylate (a) having an alkyl group having 1 to 4 carbon atoms, an alkyl (meth)acrylate having an alkyl group having 4 carbon atoms is preferred, and butyl acrylate is particularly preferred.

[0091] In addition, the (meth)acrylic acid alkyl ester (a) having an alkyl group with 1 to 4 carbon atoms is preferably used in combination with a (meth)acrylic acid alkyl ester having an alkyl group with 4 carbon atoms and a (meth)acrylic acid alkyl ester having an alkyl group with 1 to 3 carbon atoms. As the (meth)acrylic acid alkyl ester having an alkyl group with 1 to 3 carbon atoms, methyl acrylate and ethyl acrylate are preferred. In the case of the above-mentioned combination, the following mode is preferred: the above-mentioned weight ratio of the (meth)acrylic acid alkyl ester having an alkyl group with 4 carbon atoms is preferably set to 30 to 96 weight%, more preferably to 40 to 85 weight%, and on the other hand, the above-mentioned weight ratio of the (meth)acrylic acid alkyl ester having an alkyl group with 1 to 3 carbon atoms is preferably set to 4 to 50 weight%, more preferably to 5 to 20 weight%, and the total is adjusted to 80 weight% or more.

[0092] It should be noted that, for the purpose of improving adhesion and heat resistance, in addition to the monomer unit of the (meth)acrylic acid alkyl ester (a) having an alkyl group having 1 to 4 carbon atoms, one or more comonomers having a polymerizable functional group having an unsaturated double bond such as a (meth)acryloyl group or a vinyl group may be introduced by copolymerization in the (meth)acrylic polymer (A). The weight ratio of the comonomer is 20% by weight or less.

[0093] However, when the polymerization ratio of the alkyl (meth)acrylate having an alkyl group with 5 or more carbon atoms increases, it is not preferred from the viewpoint of suppressing the peeling of the above-mentioned adhesive. Therefore, the polymerization ratio of the alkyl (meth)acrylate having an alkyl group with 5 or more carbon atoms is preferably 20% by weight or less, more preferably 15% by weight or less, further preferably 10% by weight or less, further preferably 5% by weight or less, further preferably 3% by weight or less, further preferably 1% by weight or less, and most preferably not used.

[0094] As the above-mentioned comonomer, for example, an aromatic ring-containing (meth)acrylate can be used. The aromatic ring-containing (meth)acrylate is a compound containing an aromatic ring structure and a (meth)acryloyl group in its structure. Examples of the aromatic ring include a benzene ring, a naphthalene ring, and a biphenyl ring.

[0095] Specific examples of the aromatic ring-containing (meth)acrylate include benzyl (meth)acrylate, phenyl (meth)acrylate, o-phenylphenol (meth)acrylate, phenoxymethyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypropyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, ethylene oxide-modified nonylphenol (meth)acrylate, ethylene oxide-modified cresol (meth)acrylate, phenol ethylene oxide-modified (meth)acrylate, 2-hydroxy (meth)acrylate, (Meth)acrylates having a benzene ring, such as -3-phenoxypropyl, methoxybenzyl (meth)acrylate, benzyl (meth)acrylate chloride, toluene (meth)acrylate, styrene (meth)acrylate; (meth)acrylates having a naphthalene ring, such as hydroxyethylated β-naphthol acrylate, 2-naphthylethyl (meth)acrylate, 2-naphthyloxyethyl acrylate, 2-(4-methoxy-1-naphthyloxy)ethyl (meth)acrylate; (meth)acrylates containing an aromatic ring, such as biphenyl (meth)acrylate, having a biphenyl ring.

[0096] As the aromatic ring-containing (meth)acrylate, benzyl (meth)acrylate and phenoxyethyl (meth)acrylate are preferred from the viewpoint of adhesive properties and durability, and phenoxyethyl (meth)acrylate is particularly preferred.

[0097] The weight ratio of the aromatic ring-containing (meth)acrylate is 20% by weight or less, preferably 3 to 18% by weight, more preferably 5 to 16% by weight, and still more preferably 10 to 14% by weight. When the weight ratio of the aromatic ring-containing (meth)acrylate is 3% by weight or more, it is preferred from the perspective of suppressing uneven display.

[0098] Examples of the comonomer include functional group-containing monomers such as a hydroxyl group-containing monomer, a carboxyl group-containing monomer, and an amide group-containing monomer.

[0099] The hydroxyl-containing monomer is a compound containing a hydroxyl group in its structure and containing polymerizable unsaturated double bonds such as (meth)acryloyl and vinyl groups. As specific examples of hydroxyl-containing monomers, for example, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate and other hydroxyalkyl (meth)acrylates, (4-hydroxymethylcyclohexyl)methyl acrylate and the like can be cited. Among the above-mentioned hydroxyl-containing monomers, 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferred from the aspect of durability, and 4-hydroxybutyl (meth)acrylate is particularly preferred.

[0100] The carboxyl group-containing monomer is a compound containing a carbonyl group in its structure and containing polymerizable unsaturated double bonds such as (meth)acryloyl and vinyl groups. Specific examples of carboxyl group-containing monomers include (meth)acrylic acid, (meth)carboxyethyl acrylate, (meth)carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, etc. Among the above-mentioned carboxyl group-containing monomers, acrylic acid is preferred from the viewpoints of copolymerizability, price and adhesive properties.

[0101] When the adhesive composition contains a crosslinking agent, the hydroxyl-containing monomer and the carboxyl-containing monomer become reaction sites with the crosslinking agent. The hydroxyl-containing monomer and the carboxyl-containing monomer are highly reactive with the intermolecular crosslinking agent and are therefore preferably used to improve the cohesiveness and heat resistance of the resulting adhesive layer.

[0102] The weight ratio of the hydroxyl-containing monomer is preferably 3% by weight or less, more preferably 0.01 to 3% by weight, further preferably 0.1 to 2% by weight, and further preferably 0.2 to 2% by weight. From the viewpoint of crosslinking the adhesive layer, and from the perspective of durability and adhesive properties, the weight ratio of the hydroxyl-containing monomer is preferably set to 0.01% by weight or more. On the other hand, when it exceeds 3% by weight, it is not preferred from the perspective of durability.

[0103] The weight ratio of the carboxyl group-containing monomer is preferably 10 wt% or less, more preferably 0.01 to 8 wt%, further preferably 0.05 to 6 wt%, and further preferably 0.1 to 5 wt%. In view of durability, the weight ratio of the carboxyl group-containing monomer is preferably 0.01 wt% or more.

[0104] The amide group-containing monomer is a compound containing an amide group in its structure and containing a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Specific examples of the amide group-containing monomer include: (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropylacrylamide, N-methyl(meth)acrylamide, N-butyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methylol-N-propane(meth)acrylamide, aminomethyl(meth)acrylamide, aminoethyl(meth)acrylamide, mercaptomethyl(meth)acrylamide, mercaptoethyl(meth)acrylamide, and other acrylamide monomers; N-(meth)acryloylmorpholine, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, and other N-vinyl-containing lactam monomers, etc. Amide group-containing monomers are preferred from the viewpoint of suppressing the increase of surface resistance over time (especially in a humidified environment) and satisfying durability. Among the amide group-containing monomers, N-vinyl lactam-containing monomers are particularly preferred.

[0105] When the weight ratio of the amide group-containing monomer increases, there is a tendency for the anchoring property to the optical film to decrease, so the weight ratio is preferably 10% by weight or less, and more preferably 5% by weight or less. From the viewpoint of suppressing the increase of the surface resistance value over time (especially in a humidified environment), it is preferably 0.1% by weight or more. The weight ratio is preferably 0.3% by weight or more, and more preferably 0.5% by weight or more.

[0106] Specific examples of other copolymer monomers other than those mentioned above include anhydride group-containing monomers such as maleic anhydride and itaconic anhydride; caprolactone adducts of acrylic acid; sulfonic acid group-containing monomers such as allyl sulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, and (meth)acrylate sulfopropyl ester; phosphate group-containing monomers such as 2-hydroxyethylacryloyl phosphate, etc.

[0107] Examples of monomers for modification include: alkylaminoalkyl (meth)acrylates such as aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, and tert-butylaminoethyl (meth)acrylate; alkoxyalkyl (meth)acrylates such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexam ... Succinimide monomers such as succinimide (methyl) acryloyl-8-oxyoctamethylene succinimide; maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; itaconimide monomers such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-laurylitaconimide.

[0108] In addition, as the modifying monomer, vinyl monomers such as vinyl acetate and vinyl propionate; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; epoxy group-containing (meth)acrylates such as glycidyl (meth)acrylate; glycol (meth)acrylates such as polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate; acrylate monomers such as tetrahydrofurfuryl (meth)acrylate, fluorine-containing (meth)acrylate, silicone (meth)acrylate, 2-methoxyethyl acrylate, etc. can also be used. In addition, isoprene, butadiene, isobutylene, vinyl ether, etc. can be cited.

[0109] In addition, as copolymerizable monomers other than the above, silane monomers containing silicon atoms can also be mentioned. As silane monomers, for example, 3-acryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 4-vinylbutyltrimethoxysilane, 4-vinylbutyltriethoxysilane, 8-vinyloctyltrimethoxysilane, 8-vinyloctyltriethoxysilane, 10-methacryloxydecyltrimethoxysilane, 10-acryloxydecyltrimethoxysilane, 10-methacryloxydecyltriethoxysilane, 10-acryloxydecyltriethoxysilane, etc. can be mentioned.

[0110] The ratio of the above-mentioned other copolymerizable monomers in the (meth)acrylic polymer (A) is preferably about 0 to 10 wt %, more preferably about 0 to 7 wt %, and even more preferably about 0 to 5 wt %, based on the weight ratio of all the constituent monomers (100 wt %) of the above-mentioned (meth)acrylic polymer (A).

[0111] In addition, as the comonomer, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, Polyfunctional monomers having two or more unsaturated double bonds such as (meth)acrylic acid and vinyl groups, such as esters of (meth)acrylic acid and polyols such as caprolactone-modified dipentaerythritol hexa(meth)acrylate, and polyester (meth)acrylates, epoxy (meth)acrylates, urethane (meth)acrylates, etc. obtained by adding two or more unsaturated double bonds such as (meth)acrylic acid and vinyl groups as the same functional groups as the monomer components to the backbone of polyester, epoxy, urethane, etc.

[0112] When the above-mentioned multifunctional monomers are used as the above-mentioned comonomers, the multifunctional monomers function as crosslinking components. The amount of the above-mentioned multifunctional monomers varies according to their molecular weight, number of functional groups, etc., but relative to a total of 100 parts by weight of the monofunctional monomers, it is preferably used with less than 1 part by weight, more preferably less than 0.5 parts by weight. In addition, as its lower limit, it is not particularly limited, preferably more than 0 parts by weight, more preferably more than 0.01 parts by weight. By making the amount of the multifunctional monomers within the above range, the bonding force can be improved.

[0113] The weight average molecular weight of the (meth) acrylic polymer (A) of the present invention is generally preferably 1 million to 2.5 million. If durability, especially heat resistance, is taken into consideration, the weight average molecular weight is preferably 1.2 million to 2 million. When the weight average molecular weight is 1 million or more, it is preferred in terms of heat resistance. In addition, when the weight average molecular weight is greater than 2.5 million, there is a tendency for the adhesive to harden easily and peeling occurs easily. In addition, the weight average molecular weight (Mw) / number average molecular weight (Mn) representing the molecular weight distribution is preferably 1.8 or more and 10 or less, more preferably 1.8 to 7, and further preferably 1.8 to 5. When the molecular weight distribution (Mw / Mn) is greater than 10, it is not preferred in terms of durability. It should be noted that the weight average molecular weight and the molecular weight distribution (Mw / Mn) are determined by GPC (gel permeation chromatography) and calculated by polystyrene conversion.

[0114] Such (meth)acrylic polymer (A) can be produced by appropriately selecting a known production method such as solution polymerization, bulk polymerization, emulsion polymerization, various free radical polymerizations such as radiation (UV) polymerization, etc. The obtained (meth)acrylic polymer (A) may be any copolymer such as a random copolymer, a block copolymer, or a graft copolymer.

[0115] It should be noted that in solution polymerization, as a polymerization solvent, for example, ethyl acetate, toluene, etc. can be used. As a specific solution polymerization example, the reaction is carried out under a stream of an inert gas such as nitrogen, with a polymerization initiator added, usually at about 50 to 70° C. for about 5 to 30 hours.

[0116] The polymerization initiator, chain transfer agent, emulsifier, etc. used in the free radical polymerization are not particularly limited and can be appropriately selected for use. It should be noted that the weight average molecular weight of the (meth)acrylic polymer (A) can be controlled by the amount of the polymerization initiator and chain transfer agent, the reaction conditions, etc., and their amounts can be appropriately adjusted according to their types.

[0117] In addition, the adhesive composition forming the adhesive layer of the present invention preferably contains a silane coupling agent (B) as an additive. Preferably, the silane coupling agent (B) contains at least one selected from a low molecular weight (non-oligomer type) epoxy-containing silane coupling agent (b1) and an oligomer type mercapto-containing silane coupling agent (b2). By combining the above-mentioned silane coupling agent (B) with a (meth)acrylic polymer (A) containing 80% by weight or more of the above-mentioned (meth)acrylic acid alkyl ester (a) having an alkyl group with 1 to 4 carbon atoms as a monomer unit, the peeling of the adhesive layer can be suppressed even in a humidified environment where there is a concern that grease and paste components will come into contact with the above-mentioned elastic intermediate layer.

[0118] As low molecular weight epoxy-containing silane coupling agents (b1), for example: 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, etc. can be cited. In addition, as oligomer-type mercapto-containing silane coupling agents (b2), for example: X-41-1805 and X-41-1810 manufactured by Shin-Etsu Chemical Co., Ltd. can be cited. These silane coupling agents having multiple alkoxysilyl groups in the molecule are not easy to volatilize, and are preferably used because they effectively improve durability due to having multiple alkoxysilyl groups. In particular, for the adherend of an optical film with an adhesive, durability is also suitable in the case of a transparent conductive layer (for example, ITO, etc.) in which alkoxysilyl groups are less likely to react than glass.

[0119] The silane coupling agent (B) may be a low molecular weight (non-oligomer type) epoxy group-containing silane coupling agent (b1) or an oligomer type mercapto group-containing silane coupling agent (b2) alone, or two or more thereof may be mixed and used. The total content thereof is preferably 0.01 to 5 parts by weight, more preferably 0.02 to 3 parts by weight, further preferably 0.05 to 1 part by weight, and further preferably 0.1 to 0.8 parts by weight, relative to 100 parts by weight of the (meth)acrylic polymer (A).

[0120] As the silane coupling agent (B), other silane coupling agents other than those mentioned above may also be used. Examples of other low molecular weight silane coupling agents include amino group-containing silane coupling agents such as 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylene)propylamine, and N-phenyl-γ-aminopropyltrimethoxysilane, (meth)acryl group-containing silane coupling agents such as 3-acryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane, and isocyanate group-containing silane coupling agents such as 3-isocyanatepropyltriethoxysilane. Examples of other oligomer-type silane coupling agents include X-41-1053, X-41-1059A, X-41-1056, X-41-1818, and X-40-2651 manufactured by Shin-Etsu Chemical Co., Ltd. These other silane coupling agents are preferably used in an amount of 3 parts by weight or less, and in an amount equal to or less than that of the silane coupling agents (b1) and (b2), relative to 100 parts by weight of the (meth)acrylic polymer (A).

[0121] The adhesive composition of the present invention may contain a crosslinking agent (C). As the crosslinking agent (C), an organic crosslinking agent or a polyfunctional metal chelate can be used. Examples of organic crosslinking agents include isocyanate crosslinking agents, peroxide crosslinking agents, epoxy crosslinking agents, imine crosslinking agents, and the like. Polyfunctional metal chelates are formed by covalent bonding or coordination bonding of polyvalent metals and organic compounds. Examples of polyvalent metal atoms include Al, Cr, Zr, Co, Cu, Fe, Ni, V, Zn, In, Ca, Mg, Mn, Y, Ce, Sr, Ba, Mo, La, Sn, Ti, and the like. Examples of atoms in organic compounds that are covalently bonded or coordinately bonded include oxygen atoms, and examples of organic compounds include alkyl esters, alcohol compounds, carboxylic acid compounds, ether compounds, ketone compounds, and the like.

[0122] As the crosslinking agent (C), an isocyanate crosslinking agent is preferred. As the isocyanate crosslinking agent, a compound having at least two isocyanate groups can be used. For example, known aliphatic polyisocyanates, alicyclic polyisocyanates, aromatic polyisocyanates, etc., which are commonly used in urethanization reactions, can be used.

[0123] The amount of the crosslinking agent (C) used is preferably 3 parts by weight or less, more preferably 0.01 to 3 parts by weight, further preferably 0.02 to 2 parts by weight, and further preferably 0.03 to 1 part by weight, relative to 100 parts by weight of the (meth)acrylic polymer (A). It should be noted that when the crosslinking agent (C) is less than 0.01 parts by weight, the adhesive becomes insufficiently crosslinked, and there is a concern that the durability and adhesive properties cannot be satisfied. On the other hand, when it is more than 3 parts by weight, the adhesive becomes too hard and the durability tends to decrease.

[0124] The adhesive composition of the present invention may further contain other known additives, such as antistatic agent, colorant, pigment powder, dye, surfactant, plasticizer, tackifier, surface lubricant, leveling agent, softener, antioxidant, anti-aging agent, light stabilizer, ultraviolet absorber, polymerization inhibitor, inorganic or organic filler, metal powder, granular, foil, etc., according to the application. In addition, within a controllable range, redox type with the addition of a reducing agent may also be used. These additives are preferably used in an amount of 5 parts by weight or less, more preferably 3 parts by weight or less, and further preferably 1 part by weight or less relative to 100 parts by weight of the (meth) acrylic polymer (A).

[0125] On the other hand, it is preferred that the adhesive composition of the present invention does not contain a polyether compound having a polyether skeleton and having a reactive silyl group at at least one terminal. Examples of the polyether compound having a reactive silyl group include the polyether compounds disclosed in Japanese Patent Application Laid-Open No. 2010-275522. The polyether compound having a reactive silyl group is preferred from the viewpoint of improving reworkability, but is not preferred from the viewpoint of suppressing adhesive peeling in a humidified environment where there is a concern that grease or paste components may come into contact with the elastic intermediate layer.

[0126] The pressure-sensitive adhesive layer of the present invention can be used as a pressure-sensitive adhesive layer-attached optical film (including at least one polarizing film). The pressure-sensitive adhesive layer-attached optical film can be obtained by forming a pressure-sensitive adhesive layer on at least one surface of an optical film using the pressure-sensitive adhesive composition.

[0127] As a method for forming an adhesive layer, the following methods can be used: for example, the adhesive composition is applied to a separator that has been subjected to a peeling treatment, and after drying to remove the polymerization solvent, etc. to form an adhesive layer, the adhesive layer is transferred to an optical film (polarizing film); or, the adhesive composition is applied to an optical film (polarizing film), and the polymerization solvent is dried to remove the polymerization solvent, etc. to form an adhesive layer on the optical film, etc. It should be noted that when applying the adhesive, one or more solvents other than the polymerization solvent may be newly added.

[0128] The thickness of the adhesive layer is not particularly limited. If it is thinner, the adhesion with the image display portion is reduced and it tends to be easily peeled off during heat shrinkage. On the other hand, if it is thicker, it is not easily absorbed by the adhesive in a humidified environment where there is a concern that grease and paste components will come into contact with the elastic intermediate layer, and it becomes easy to peel off. Therefore, for example, it is preferably about 10 to 30 μm, and more preferably 15 to 20 μm.

[0129] The oleic acid swelling degree of the above-mentioned adhesive layer is greater than 130% and is less than 190%. According to the image display panel of the present invention, when the oleic acid swelling degree of the adhesive layer exceeds 130%, further when it is greater than 140%, and further when it is greater than 150%, the influence of grease and paste components on the adhesive layer can be suppressed to a smaller level. In addition, when the oleic acid swelling degree of the adhesive layer exceeds 130%, the influence of grease and paste components absorbed by the adhesive layer on other optical components (films, substrates, wiring, etc. on the lower side of the panel) can be reduced. On the other hand, when the oleic acid swelling degree of the adhesive layer increases, the influence of the adhesive layer on grease and paste components also increases. Therefore, the oleic acid swelling degree is less than 190%, and more preferably less than 180%.

[0130] <Image display unit>

[0131] The image display unit together with the above-mentioned optical film (including at least one polarizing film) forms a part of the image display device. Examples of the image display device include liquid crystal display devices, organic EL (organic electroluminescence) display devices, PDP (plasma display panel), electronic paper, etc.

[0132] The image display unit may be a liquid crystal cell used in a liquid crystal display device. The liquid crystal cell may be any type of liquid crystal cell such as TN type, STN type, π type, VA type, IPS type, etc.

[0133] <Image display panel>

[0134] When forming an image display panel, in addition to the above-mentioned optical films, other optical films may be stacked and used according to the adaptability of their respective configuration positions. For example, in a liquid crystal display panel, at least a polarizing film is arranged on the side opposite to the visible side of the liquid crystal unit, and there is no particular restriction on the polarizing film. In addition, as the above-mentioned other optical films, for example, reflective plates, anti-transmission plates, phase difference films (including 1 / 2 wave plates, 1 / 4 wave plates, etc.), visual compensation films, brightness enhancement films, etc., which are optical films as optical layers sometimes used in the formation of liquid crystal display devices, etc., can be cited. These other optical films can be used in one layer or two layers or more.

[0135] The end face of the image display panel of the present invention is formed into a plane. Preferably, the entire surface of the end face is formed into a plane. As a method for making the end face into a plane, a method of cutting the end of the obtained image display panel by laser cutting, a Thomson processing method, a slit processing method, an end grinding processing method, etc. can be cited.

[0136] <Outer frame, inner frame>

[0137] The outer frame forms an outer frame outside the end face of the image display panel for protection, and the outer frame used for the image display panel can be used without special restrictions. In addition, the inner frame protects the outermost surface of the end face of the image display panel, and the inner frame used for the image display panel can be used without special restrictions.

[0138] <Elastic middle layer>

[0139] As described above, the elastic intermediate layer is used to avoid direct contact between the image display panel and the main body of the image display device. As long as it is a material that can alleviate the impact caused by the above contact when the notebook computer is closed, there is no particular restriction. As the material forming the elastic intermediate layer, for example, rubber materials such as nitrile rubber, fluororubber, urethane rubber, silicone rubber, ethylene-propylene rubber, hydrogenated nitrile rubber, chloroprene rubber, acrylic rubber, butyl rubber, chlorosulfonated polyethylene, epichlorohydrin rubber, and natural rubber used for rubber seals can be used. In addition, as the material of the elastic intermediate layer, for example, elastic plastics such as vinyl chloride resin and urethane resin, and foamed foam of cushion pads can be listed.

[0140] <Image display device>

[0141] The formation of various image display devices such as the liquid crystal display device of the present invention can be carried out according to existing methods. It is formed by appropriately assembling and introducing components such as the lighting system used as needed into a driving circuit. In general, a liquid crystal display device is formed by configuring a liquid crystal unit (composed of a glass substrate / liquid crystal layer / glass substrate) on polarizing films on both sides thereof, and components such as the lighting system used as needed, and appropriately assembling and introducing them into a driving circuit. The above-mentioned optical film is configured on the visible side, and other polarizing films are configured on the other side. In addition, for the liquid crystal display device, a suitable liquid crystal display device such as a liquid crystal display device using a backlight or a reflector in the lighting system can be formed. In addition, when forming a liquid crystal display device, for example, one or more layers of a diffusion sheet, an anti-glare layer, an anti-reflection film, a protective sheet, a prism array, a lens array sheet, a light diffusion sheet, a backlight, and other suitable components can be configured at appropriate positions.

[0142] Example

[0143] The present invention is specifically described below by manufacturing examples and embodiments, but the present invention is not limited to these embodiments. It should be noted that the parts and % in each example are weight basis. The room temperature conditions are 23°C and 65%RH unless otherwise specified.

[0144] <Measurement of Weight Average Molecular Weight of (Meth)Acrylic Polymer (A)>

[0145] The weight average molecular weight (Mw) of the (meth)acrylic polymer was measured by GPC (gel permeation chromatography). Mw / Mn was measured in the same manner.

[0146] Analytical device: HLC-8120GPC manufactured by Tosoh Corporation

[0147] ·Pillar: Made by Tosoh Corporation, G7000H XL +GMH XL +GMHXL

[0148] · Pillar size: 7.8mm φ x 30cm, total 90cm

[0149] Column temperature: 40℃

[0150] Flow rate: 0.8mL / min

[0151] Injection volume: 100μL

[0152] ·Eluent: Tetrahydrofuran

[0153] Detector: Differential Refractometer (RI)

[0154] Standard sample: polystyrene

[0155] <Preparation of optical films>

[0156] Optical films A to D used in Examples, Comparative Examples, and Reference Examples were prepared as follows.

[0157] (Manufacturing of thin polarizer)

[0158] A single surface of an amorphous isophthalic acid copolymer polyethylene terephthalate (IPA copolymer PET) film substrate (thickness: 100 μm) having a water absorption of 0.75% and a Tg of 75°C was subjected to corona treatment, and an aqueous solution containing polyvinyl alcohol (degree of polymerization 4200, degree of saponification 99.2 mol%) and acetoacetyl-modified PVA (degree of polymerization 1200, acetoacetyl modification rate 4.6%, degree of saponification 99.0 mol% or more, manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER Z200") in a ratio of 9:1 was applied to the corona-treated surface at 25°C and dried to form a PVA-based resin layer with a thickness of 11 μm, thereby producing a laminate.

[0159] The obtained laminate was subjected to free-end uniaxial stretching (auxiliary stretching treatment in gas atmosphere) in which the laminate was stretched to 2.0 times in the longitudinal direction (length direction) between rolls having different peripheral speeds in an oven at 120°C.

[0160] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution prepared by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 30° C. for 30 seconds (insolubilization treatment).

[0161] Next, the polarizing plate was immersed in a dyeing solution at a temperature of 30° C. while adjusting the iodine concentration and immersion time so that the polarizing plate reached a given transmittance. In this embodiment, the polarizing plate was immersed in an iodine aqueous solution containing 0.2 parts by weight of iodine and 1.0 parts by weight of potassium iodide per 100 parts by weight of water for 60 seconds (dyeing treatment).

[0162] Next, the sample was immersed in a crosslinking bath (boric acid aqueous solution containing 3 parts by weight of potassium iodide and 3 parts by weight of boric acid per 100 parts by weight of water) at a liquid temperature of 30° C. for 30 seconds (crosslinking treatment).

[0163] Then, the laminate was immersed in an aqueous boric acid solution (an aqueous solution obtained by adding 4 parts by weight of boric acid and 5 parts by weight of potassium iodide to 100 parts by weight of water) at a liquid temperature of 70°C, and uniaxially stretched (stretching treatment in aqueous solution) along the longitudinal direction (length direction) between rollers with different circumferential speeds so that the total stretching ratio reached 5.5 times.

[0164] Then, the laminated body was immersed in a cleaning bath (an aqueous solution prepared by mixing 4 parts by weight of potassium iodide with respect to 100 parts by weight of water) at a liquid temperature of 30° C. (cleaning treatment).

[0165] Through the above operation, an optical film laminate including a polarizer having a thickness of 5 μm was obtained.

[0166] (Transparent protective film)

[0167] Acrylic: A (meth)acrylic resin film having a lactone ring structure and having a thickness of 40 μm was used after the adhesion-facilitating surface thereof was subjected to a corona treatment.

[0168] (For the production of adhesives for transparent protective films)

[0169] 10 parts by weight of N-hydroxyethyl acrylamide, 30 parts by weight of acryloyl morpholine, 45 parts of 1,9-nonanediol diacrylate, 10 parts of an acrylic oligomer obtained by polymerizing a (meth)acrylic acid monomer (ARUFONUP1190, manufactured by Toagosei Co., Ltd.), 3 parts of a photopolymerization initiator (IRGACURE907, manufactured by BASF), and 2 parts of a polymerization initiator (KAYACURE DETX-S, manufactured by Nippon Kayaku Co., Ltd.) were mixed to prepare an ultraviolet curable adhesive.

[0170] (Phase difference film)

[0171] First retardation film: A cyclic olefin-based film having a thickness of 18 μm (refractive index characteristics: nx>ny>nz, in-plane retardation: 116 nm) was used.

[0172] Second retardation film: A modified polyethylene film having a thickness of 6 μm (refractive index characteristics: nz>nx>ny, in-plane retardation: 35 nm) was used.

[0173] <Polarizing film>

[0174] The above-mentioned ultraviolet curing adhesive a was applied to the surface of the polarizer of the above-mentioned optical film laminate so that the thickness of the adhesive layer after curing reached 1 μm, and the above-mentioned transparent protective film (thickness 40 μm: acrylic) was attached at the same time, and then irradiated with ultraviolet rays as active energy rays to cure the adhesive. Ultraviolet irradiation used a metal halide lamp encapsulated with gallium, irradiation device: Light HAMMER10 manufactured by FusionUV Systems, valve: V valve, maximum illumination: 1600mW / cm 2 , cumulative exposure 1000 / mJ / cm 2 (wavelength 380 to 440 nm), and the illuminance of ultraviolet rays was measured using a Sola-Check system manufactured by Solatell Co. Next, the amorphous PET substrate was peeled off to prepare a single-side protected polarizing film using a thin polarizer.

[0175] On the other hand, the first phase difference film and the second phase difference film were sequentially laminated on the thin polarizer side after the above-mentioned amorphous PET substrate was peeled off, and a polarizing film with a thickness of 72 μm was obtained. During the lamination, an adhesive layer with a thickness of 1 μm was formed using the same ultraviolet curing adhesive a as mentioned above. It should be noted that the lamination was performed in such a way that the slow axis of the first phase difference film became 0° relative to the absorption axis of the polarizer, and the slow axis of the second phase difference film became 90° relative to the absorption axis of the polarizer.

[0176] <Preparation of film with surface treatment layer: ARTAC, thickness 44 μm)>

[0177] An antireflection layer having a film thickness of 4 μm was formed on a cellulose triacetate film having a thickness of 40 μm by sputtering.

[0178] <Production of film with surface treatment layer: ARTAC, thickness 84 μm>

[0179] An antireflection layer having a film thickness of 4 μm was formed on a cellulose triacetate film having a thickness of 80 μm by sputtering.

[0180] <Production of film with surface treatment layer: LCTAC (thickness 42 μm)>

[0181] A liquid crystal phase difference layer having a thickness of 2 μm was formed by coating on a cellulose triacetate film having a thickness of 40 μm.

[0182] <Preparation of Adhesive Layer A>

[0183] (Preparation of acrylic polymer)

[0184] A monomer mixture containing 100 parts of n-butyl acrylate and 5 parts of acrylic acid was added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser. Furthermore, 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator was added together with 100 parts of ethyl acetate to 100 parts of the above monomer mixture (solid content), and nitrogen was introduced while slowly stirring to perform nitrogen replacement. Then, the liquid temperature in the flask was maintained at around 55°C, and a polymerization reaction was performed for 8 hours to prepare a solution of an acrylic polymer with a weight average molecular weight (Mw) of 1.6 million.

[0185] (Preparation of Adhesive Composition)

[0186] 0.45 parts of an isocyanate crosslinking agent (Coronate L, trimethylolpropane toluene diisocyanate, manufactured by Tosoh Corporation) was added to 100 parts of the solid content of the acrylic polymer solution obtained above to prepare a solution of an acrylic pressure-sensitive adhesive composition.

[0187] (Formation of Adhesive Layer)

[0188] Next, the solution of the acrylic adhesive composition was applied to one side of a polyethylene terephthalate film (diaphragm: manufactured by Mitsubishi Chemical Polyester Film Co., Ltd., MRF38) treated with a silicone release agent so that the thickness of the adhesive layer after drying became 23 μm or 12 μm, and the film was dried at 155°C for 1 minute to form an adhesive layer A on the surface of the diaphragm.

[0189] The polarizing film and the film with a surface treatment layer were laminated in the following configuration to prepare optical films A to C. The lamination was performed by laminating the film with a surface treatment layer on the triacetylcellulose film side via the adhesive layer A. The polarizing film was laminated by laminating the adhesive layer A on the HTX side.

[0190] Optical film A (total thickness 128 μm): ARTAC (thickness 44 μm) / adhesive layer A (thickness 12 μm) / polarizing film (thickness 72 μm)

[0191] Optical film B (total thickness 179 μm): ARTAC (thickness 84 μm) / adhesive layer A (thickness 23 μm) / polarizing film (thickness 72 μm)

[0192] Optical film C (total thickness 244 μm): ARTAC (thickness 84 μm) / adhesive layer A (thickness 23 μm) / LCTAC (thickness 42 μm) / adhesive layer A (thickness 23 μm) / polarizing film (thickness 72 μm)

[0193] Example 1

[0194] (Preparation of acrylic polymer)

[0195] A monomer mixture containing 81.9 parts of n-butyl acrylate, 13.2 parts of benzyl acrylate, 0.1 parts of 4-hydroxybutyl acrylate, and 4.8 parts of acrylic acid was added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser. Furthermore, 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator and 100 parts of ethyl acetate were added to 100 parts of the above monomer mixture (solid content), and nitrogen was introduced while slowly stirring to perform nitrogen replacement. Then, the liquid temperature in the flask was maintained at about 55°C, and a polymerization reaction was performed for 8 hours to prepare a solution of an acrylic polymer with a weight average molecular weight (Mw) of 1.6 million.

[0196] (Preparation of Adhesive Composition)

[0197] 0.2 parts of an oligomer-type mercapto-containing silane coupling agent (X-41-1810 manufactured by Shin-Etsu Chemical Co., Ltd.) and 0.45 parts of an isocyanate crosslinking agent (Coronate L manufactured by Tosoh Corporation, trimethylolpropane toluene diisocyanate) were added to 100 parts of the solid content of the acrylic polymer solution obtained above to prepare a solution of an acrylic adhesive composition.

[0198] (Formation of Adhesive Layer)

[0199] Next, the solution of the acrylic adhesive composition was applied to one side of a polyethylene terephthalate film (separator: manufactured by Mitsubishi Chemical Polyester Film Co., Ltd., MRF38) treated with a silicone release agent and dried at 155°C for 1 minute so that the thickness of the adhesive layer after drying became 20 μm, thereby forming an adhesive layer B on the surface of the separator.

[0200] (Production of Image Display Panel)

[0201] An image display unit (including a liquid crystal cell having a diagonal size of 15 inches and a thickness of 300 μm) was prepared.

[0202] The above-prepared adhesive layer B was adhered to the polarizing film side of the above-prepared optical film A to prepare an optical film with an adhesive layer (a polarizing film with short and long sides that is 4 mm shorter than the above-mentioned liquid crystal unit). After peeling the diaphragm from the optical film with the adhesive layer, the above-mentioned optical film A (the second phase difference film side) was adhered to the visible side of the above-mentioned image display part through the adhesive layer B using a laminator to prepare an image display panel (liquid crystal display panel). Next, an autoclave treatment was performed at 50°C and 0.5MPa for 15 minutes to make the above-mentioned optical film A completely close to the image display part. The image display panel was cut by laser cutting in a manner that the entire end of the obtained image display panel formed a plane and formed into a 15-inch size.

[0203] (Manufacturing of image display panels with frames)

[0204] As the elastic intermediate layer, a rubber molded product having a width of 1 mm and a height of 5 mm processed to match the outer edge of the above-mentioned image display panel (15-inch size) was prepared.

[0205] In addition, as an outer frame, a sputtered resin plate (frame) with a metal-like texture and a width of 1 mm and a height of 3 mm was prepared to match the above-mentioned image display panel (15-inch size) (it was integrated with a concave frame frame that could be embedded in the panel).

[0206] The elastic intermediate layer is mounted on a frame body integrated with the outer frame, and then the image display panel is introduced. The elastic intermediate layer and the outer frame are sequentially mounted on the entire outer side of the end face of the image display device to produce the image display device shown in FIG. Figure 3A , Figure 3B ) is a framed image display panel having a structure as shown in FIG. In the obtained framed image display panel, the elastic intermediate layer is arranged so as to protrude 1 mm from the outermost surface of the visible side of the image display panel (optical film A). The elastic intermediate layer is a structure in contact with the end face of the image display panel. The outer frame is fixed to the elastic intermediate layer by an adhesive.

[0207] Examples 2 to 11 and Comparative Examples 1 to 17

[0208] In Example 1, the adhesive layer B was formed in the same manner as in Example 1 except that the composition or ratio of the monomer mixture used in preparing the acrylic polymer, the type or amount of the silane coupling agent used in preparing the adhesive composition, the type or amount of the crosslinking agent, or the thickness of the adhesive layer to be formed were changed as shown in Table 1. In addition, using the adhesive layer B obtained above and the optical films A to F shown in Table 1, an image display panel was produced in the same manner as in Example 1. In addition, a framed image display panel was produced in the same manner as in Example 1.

[0209] In Comparative Examples 1 to 3 and 7 to 17 (production of image display panels), image display panels with frames were produced without laser cutting (the configuration of FIG. 2 ) to form the entire end of the obtained image display panel into one plane.

[0210] Among them, Example 11 produced Figure 4 ( Figure 4A , Figure 4B) is a framed image display panel having a structure shown in FIG. In the framed image display panel, a resin plate (frame) having a width of 20 mm and a height of 2 mm and having a metallic-style sputtering is prepared as an inner frame and assembled. A gap of 15 mm is provided between the elastic intermediate layer and the end face of the image display panel. An outer frame and the elastic intermediate layer are used to ensure the size of the gap. The outer frame is fixed to the elastic intermediate layer by an adhesive. The inner frame is fixed to the outermost end of the image display panel and the elastic intermediate layer by an adhesive.

[0211] In addition, the adhesive composition used when forming the adhesive layer of Comparative Example 13 was prepared by the following method.

[0212] A monomer mixture consisting of 67 parts by weight of 2-ethylhexyl acrylate (2EHA), 15 parts by weight of 2-hydroxyethyl acrylate (HEA) and 18 parts by weight of N-vinyl-2-pyrrolidone (NVP) was mixed with 0.050 parts by weight of 1-hydroxycyclohexyl phenyl ketone (trade name: Irgacure 184, manufactured by BASF) and 0.050 parts by weight of 2,2-dimethoxy-1,2-diphenylethane-1-one (trade name: Irgacure 651, manufactured by BASF) as a photopolymerization initiator, and then irradiated with ultraviolet rays until the viscosity (measurement conditions: BH viscometer No. 5 rotor, 10 rpm, measurement temperature 30° C.) reached about 20 Pa·s, thereby obtaining a prepolymer composition (polymerization rate: 9%) in which part of the above monomer components was polymerized. Next, 0.09 parts by weight of hexanediol diacrylate (HDDA) was added to the prepolymer composition and mixed to obtain an adhesive composition. The adhesive composition was applied to the peeling-treated surface of a release film (trade name "MRF#38", manufactured by Mitsubishi Resins Co., Ltd.) to a thickness of 20 μm to form an adhesive composition layer. Next, the surface of another adhesive composition layer was attached to the peeling-treated surface of a release film ("MRN#38", manufactured by Mitsubishi Resins Co., Ltd.) under an illumination of 4 mW / cm 2 , Light intensity: 1200mJ / cm 2 The adhesive sheet was prepared by irradiating the adhesive with ultraviolet light under the conditions of .

[0213] Reference Example 1 (Manufacturing of Cover Glass / Image Display Panel)

[0214] Using the same image display panel as that prepared in Example 1, a Figure 5 An image display panel with a frame having the structure shown.

[0215] As the outer frame, the same outer frame as that used in Example 1 was prepared.

[0216] As the cover glass, a tempered glass having a thickness of 1500 μm and formed to fit the above-mentioned image display panel (15-inch size) was prepared.

[0217] The outer frame is installed on the entire outer side of the end surface of the image display panel and assembled. The outer frame is fixed to the image display panel by an adhesive. The cover glass is attached by an adhesive layer (LUCIACS CS9864 manufactured by Nitto Denko Corporation).

[0218] The image display panels with frames obtained in the above-mentioned examples, comparative examples, and reference examples were evaluated as follows. The evaluation results are shown in Table 1.

[0219] <Chemical test during humidification>

[0220] Using a 2 mL pipette, 10 mL of the following chemicals were dropped onto the inside (entire) of the elastic intermediate layer (outer frame in the reference example) of the obtained framed image display panel.

[0221] Oleic acid: oleic acid manufactured by Wako Pure Chemical Industries, Ltd. (first grade, content 65% by weight).

[0222] Vaseline moisturizing cream: UJ Body Lotion COAB (63% by weight of water, 26% by weight of glycerin) manufactured by Unilever.

[0223] Sunscreen: EDGEWELL PERSONAL CARE Banana Boat Sunscreen SPF30.

[0224] The framed image display panel was stored at 65° C. and 90% RH for 72 hours after dropping chemicals, and then left at room temperature (23° C.). The appearance was visually observed and the peeling of the adhesive layer B was evaluated according to the following criteria.

[0225] (Evaluation Criteria)

[0226] OK: No peeling.

[0227] NG: There is peeling.

[0228] <Determination of oleic acid swelling degree>

[0229] The adhesive layer B formed on the surface of the diaphragm used in each example was cut into 20 mm × 40 mm, and a sample was prepared and its weight (W1) was measured. Next, the sample was immersed in oleic acid at 60°C and 90% humidity for 24 hours, and then the sample was taken out of the oleic acid, the surface of the sample was cleaned with ethanol, and then dried at 110°C for 3 hours. The weight of the dried sample (W3) was measured, and the oleic acid swelling rate of the acrylic adhesive was calculated using the following formula (2). The weight (W2) of the diaphragm of the sample was measured separately.

[0230] Swelling ratio (weight %) = {(W3-W2) / (W1-W2)}×100

[0231] <Impact on other components>

[0232] The image display panels with frames after the evaluation were visually observed for film deterioration and wiring failure (discoloration, disconnection), and operation failure was evaluated based on the following criteria.

[0233] (Evaluation Criteria)

[0234] OK: No adverse condition.

[0235] NG: There is an adverse condition.

[0236]

[0237] The abbreviations in Table 1 represent the following substances:

[0238] MA: methyl acrylate,

[0239] EA: Ethyl acrylate,

[0240] BA: Butyl acrylate,

[0241] MMA: methyl methacrylate,

[0242] 2EHA: 2-ethylhexyl acrylate,

[0243] BzA: benzyl acrylate,

[0244] 4HBA: 4-Hydroxybutyl acrylate,

[0245] HEA: 2-hydroxyethyl acrylate,

[0246] NVP: N-vinyl pyrrolidone,

[0247] AA: acrylic acid,

[0248] SAT: SILYL SAT10 manufactured by KANEKA Corporation,

[0249] KBM403: KBM-403 manufactured by Shin-Etsu Chemical Co., Ltd.

[0250] KBM573: KBM-573 manufactured by Shin-Etsu Chemical Co., Ltd.

[0251] A100: A100 manufactured by Soken Chemical Co., Ltd. (containing acetoacetyl silane coupling agent),

[0252] X-41-1810: Oligomer-type mercapto-containing silane coupling agent manufactured by Shin-Etsu Chemical Co., Ltd.

[0253] X-41-1056: An oligomer-type epoxy-containing silane coupling agent manufactured by Shin-Etsu Chemical Co., Ltd.

[0254] C / HX: isocyanate crosslinking agent (Coronate HX manufactured by Tosoh Corporation, isocyanurate of hexamethylene diisocyanate),

[0255] C / L: isocyanate crosslinking agent (Coronate L manufactured by Tosoh Corporation, trimethylolpropane toluene diisocyanate),

[0256] D160N: Isocyanate crosslinking agent (Takenate D160N manufactured by Mitsui Chemicals, Inc., trimethylolpropane hexamethylene diisocyanate)

[0257] HDDA: Hexanediol diacrylate.

Claims

1. An image display panel with an external frame, wherein the external frame is arranged outside the end surface of the image display panel, The image display panel comprises: An image display unit, and an optical film including a polarizing film, wherein the optical film is arranged on the visible side of the image display portion via an adhesive layer, in, The outer frame is provided on at least a portion of the outer side of the end surface of the image display panel via the outermost elastic intermediate layer protruding from the visible side of the image display panel so as not to cover the elastic intermediate layer. The oleic acid swelling degree of the adhesive layer is greater than 130% and less than 190%, The end surface of the image display panel is formed as a plane.

2. The image display panel with an outer frame according to claim 1, wherein: The polarizing film has a transparent protective film on one side or both sides of a polarizer, and the thickness of the polarizer is 3 to 30 μm.

3. The image display panel with an outer frame according to claim 1, wherein: The optical film has a surface treatment layer on the outermost surface on the viewing side.

4. The image display panel with an outer frame according to claim 1, wherein: The distance from the outermost surface of the visible side of the image display panel to the adhesive layer is 75 μm or more.

5. The image display panel with an outer frame according to claim 1, wherein: The distance from the outermost surface of the visible side of the image display panel to the adhesive layer is 300 μm or less.

6. The image display panel with an outer frame according to claim 1, wherein: The thickness of the adhesive layer is 10 to 30 μm.

7. The image display panel with an outer frame according to claim 1, wherein: The pressure-sensitive adhesive layer is formed from a pressure-sensitive adhesive composition containing a (meth)acrylic polymer (A) as a base polymer.

8. The image display panel with an outer frame according to claim 7, wherein: The adhesive composition contains a silane coupling agent (B).

9. The image display panel with an outer frame according to claim 1, wherein: An end surface of the image display panel is in contact with the elastic intermediate layer.

10. The image display panel with an outer frame according to claim 1 or 9, wherein: An inner frame is provided on the outermost surface of the end surface portion of the image display panel which is located on the inner side of the elastic intermediate layer, and the elastic intermediate layer protrudes from the inner frame. 11 . An image display device comprising the image display panel with an outer frame according to claim 1 .

Citation Information

Patent Citations

  • Production and use of clear heat-resistant resin

    JP2000230016A

  • Method of manufacturing for transparent heat resistant resin and use of the same

    JP2001151814A

  • Transparent thermoplastic resin laminate

    JP2002120326A

  • Thermoplastic resin laminate

    JP2002254544A

  • Lactone ring-containing polymer, and its manufacturing method and application

    JP2005146084A